Introduction: Justice, Ethics, and Interdisciplinary Teaching and Practice - Karen Tokarz (Washington University Journal of Law & Policy, 2004)
The idea of interdisciplinary legal education has become increasingly popular in recent years, touted both in academia and in professional spheres as a means to better teaching and learning, better preparation of graduates for both specialization and interdisciplinary collaboration, and better delivery of services and justice. The initial push for interdisciplinary legal education dates back a century or more. While early advocacy for interdisciplinary legal education came primarily from legal theoreticians with opposition by practitioners, today clinical law faculty are among the most ardent supporters. Law schools have explored various approaches to importing expertise from other disciplines into legal education, from the inclusion of non-law materials in legal casebooks, to the addition of social scientists and economists to law school faculties, to collaboration with other disciplines for joint seminars and clinical courses, to joint degree programs. Yet, there has been little systematic examination of the goals and challenges of interdisciplinary legal education, how best to structure these efforts to achieve intended objectives, ways that interdisciplinary collaborations can advance or impede the delivery of services and justice, and the potential impact on each discipline’s professional roles and ethical obligations.
Keywords: Interdisciplinary approach in education; Legal ethics; Justice; Law – Study & amp; teaching